Changing Demographic Profiles of Patients With Traumatic Brain Injury: An Aging Concern - Liew, Terence Yi Song; Ng, Jun Xuan; Jayne, Chan Hui Zhen; Ragupathi, Tharun; Teo, Colin Kok Ann; Yeo, Tseng Tsai (Frontiers in Surgery, 2019)
Background Trauma continues to be a common cause of mortality in Singapore. By understanding the epidemiology of Traumatic Brain Injury (TBI), healthcare professionals can be better equipped to tackle the increasing socioeconomic burden of disease, adopting better strategies in healthcare planning. Methodology A retrospective review of 367 patients admitted with TBI to a tertiary medical institution from January to December 2014 was performed, studying demographic profiles, injury details and outcomes of these patients. Data was retrieved from the National Trauma Registry and the institution’s database. Results 234 of the 367 patients included in this study fell into two age groups — 19 to 40 years and ≥65 years. 58% of the TBI population were aged >60. Predominant mechanism of injuries in these groups were road traffic accidents and unwitnessed falls respectively. 39% of the Elderly group were on antiplatelet/anticoagulant agents (p<0.001). While aggressive surgical intervention was more common in younger patients (p<0.001), the elderly group had significantly longer lengths of hospital stay (p<0.001). Though Glasgow Outcome Scale (GOS) scores at discharge were not significantly different between the two groups, elderly patients showed greater percentages of post-injury improvement subsequently. Conclusion The demographics of TBI patients appears to have shifted towards an older population as compared to a decade ago, with an increased incidence of falls, highlighting a huge healthcare concern. We hope that this study will drive further nationwide studies in future, looking at the incidence and prevalence of TBI, and with the focus on tackling preventable causes of TBI.